The Requirement of Using Educational Platform in Educational Process from School Principals Perspective in Ajloun Directorate - Wahsheh, Nadia Abdullah Altlab (Journal of Educational and Psychological Sciences, 2022)
This Study aimed to identify the requirement of using educational platform in educational process from school principals perspective in Ajloun directorate, the researcher used the Descriptive approaches, study Sample consisted from (110) Female and male principals, chosen randomly, to collect data Questioner used, which consisted (24) paragraph Divided to three sector, the result of SPSS analysis shown that the degree of importance of the requirement of using educational platform in educational process from school principals perspective in Ajloun directorate was High, These requirements are "human" requirements and obtained the highest importance with an arithmetic average of "4.11", and "software technical structure" requirements with an arithmetic average of "4.00", then "technical" requirements with an arithmetic average, all of which are of high importance. The finding also showed there is no statistically significant differences at (α≤0.05) refers to principal sex (male and female) in addition there were statistically significant differences between the principals years of experience in favor of (less than 10 years). The researcher recommends the necessity of providing the infrastructure for employing electronic educational platforms for the teacher and student.